2022
DOI: 10.1155/2022/1413597
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of the Age and Gender Based on Human Face Images Based on Deep Learning Algorithm

Abstract: In recent times, nutrition recommendation system has gained increasing attention due to their need for healthy living. Current studies on the food domain deal with a recommendation system that focuses on independent users and their health problems but lack nutritional advice to individual users. The proposed system is developed to suggest nutritional food to people based on age and gender predicted from their face image. The designed methodology preprocesses the input image before performing feature extraction… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
2
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(6 citation statements)
references
References 60 publications
0
6
0
Order By: Relevance
“…We are interested in combining the Inception-v3 model and the support vector machine (SVM) algorithm, using polynomial, radial basis function (RBF), and sigmoid kernel functions, in facial image-based gender classification. Recent research on facial image-based gender classification we found included: a gender classification using the logistic regression, support vector machine, K-nearest neighbors, naive-Bayes, and decision trees with a FaceNet Inception network embedded facial image, where the average accuracy obtained from this research is 92.084% [6], an emotion, age group and gender classification using the convolutional neural network model with cropped facial image, where the gender classification shows an excellent performance with an accuracy value of 96.65% [7], and the gender prediction using a combination of Inception V3 network and support vector algorithm, where the results show that this combination gave an accuracy value of 93.61% [8]. These results indicate that combining the convolutional neural networks and machine learning algorithms has an excellent performance in classifying human gender based on an input of facial images.…”
Section: Imentioning
confidence: 76%
“…We are interested in combining the Inception-v3 model and the support vector machine (SVM) algorithm, using polynomial, radial basis function (RBF), and sigmoid kernel functions, in facial image-based gender classification. Recent research on facial image-based gender classification we found included: a gender classification using the logistic regression, support vector machine, K-nearest neighbors, naive-Bayes, and decision trees with a FaceNet Inception network embedded facial image, where the average accuracy obtained from this research is 92.084% [6], an emotion, age group and gender classification using the convolutional neural network model with cropped facial image, where the gender classification shows an excellent performance with an accuracy value of 96.65% [7], and the gender prediction using a combination of Inception V3 network and support vector algorithm, where the results show that this combination gave an accuracy value of 93.61% [8]. These results indicate that combining the convolutional neural networks and machine learning algorithms has an excellent performance in classifying human gender based on an input of facial images.…”
Section: Imentioning
confidence: 76%
“…We use six pre-built, CNNs with weights that have been trained on ImageNet. With the use of a transfer learning technique, technique to extract features from preprocessed hand photos [25]. CNN architectures like VGG16, DeseNet121, MobileNet, NASNet, Xception, and EfficientNet are used in the suggested work [26].…”
Section: Literature Reviewmentioning
confidence: 99%
“…A real-time fraud detection technique based on recurrent neural networks was suggested by Wang et al [16]. Many researchers use CNN in various applications [17][18][19]. Suresh Kumar et al, [20] in their study seek to forecast the occurrence of fraud using different machine learning algorithms such as support vector machine (SVM), k-nearest neighbour (KNN), and artificial neural network (ANN).…”
Section: Related Workmentioning
confidence: 99%